Effects of Some Drugs on Enzymatic Activity of Glucose 6-Phosphate Dehydrogenase from Chicken Erythrocytes in vitro - CIFTCI, MEHMET; BEYDEMIR, SUKRU; EKINCI, DENIZ (Asian Journal of Chemistry, 2010)
in vitro inhibitory effects of some important drugs on glucose 6-phosphate dehydrogenase, the NADP+ depending enzyme, from the chicken erythrocytes were investigated in the peresent study. Chicken erythrocytes glucose-6-phosphate dehydrogenase (D-glucose-6-phosphate: NADP+ oxidoreductase, EC 1.1.1.49) (G6PD) was purified by using 2',5'-ADP Sepharose 4B affinity chromatography. During the overall purification steps, the enzyme having a specific activity of 17.90 EU/mg proteins was obtained 5343-fold with a yield of 52 %. A constant temperature (4 °C) was maintained during the purification process. Enzyme activity was determined with the Beutler's method by using a spectrophotometer at 340 nm. This method was utilized for all kinetic studies. Then, metamizol, ceftriaxone, prilocaine, meloksikam, lidocaine were investigated for in vitro inhibition of this NADP+ depending enzyme. The enzyme was strongly inhibited by these drugs. In addition, I50 values of the drugs were determined by plotting activity % vs. drug concentrations. I50 values were 0.57 mM for metamizol, 0.33 mM for ceftriaxone, 28.17 mM for prilocaine, 0.0012 mM for meloksikam and 1.54 mM for lidocaine.